Physical Quality of Eggs in Pengging Duck (Anas platyrinchos) after Administration of Nanochitosan as a Feed Additive: Nanochitosan as feed additives in duck egg production - SUNARNO; NURUL ANNISA; SRI ISDADIYANTO (Borneo Journal of Resource Science and Technology, 2023)
The problem often encountered by laying duck breeders is a decrease in the physical quality of eggs. Nanochitosan is a polysaccharide that has the potential as a feed additive to improve the physical quality of eggs in pengging ducks. The use of nanochitosan at levels of 2.5, 5.0, 7.5 and 10.0 g/kg of feed can improve digestive performance and nutrient absorption in ducks. The purpose of this study was to determine the effect of nanochitosan as a feed additive on the physical quality of eggs in pengging ducks. This study used a completely randomised design with five groups and five ducks per group. The treatments consist of control and the addition of nanochitosan as a feed additive with a concentration of 2.5, 5.0, 7.5 and 10.0 g/kg of feed. The variables observed in this study included the haugh unit (HU), yolk index (IKT), yolk weight, white weight, egg weight, shell thickness, and egg shape index. The research data were analysed using ANOVA with a significance level of 5%. The results showed that the addition of nanochitosan at different levels (2.5, 5.0, 7.5 and 10.0 g/kg of feed) had a significant effect on the measured egg quality consisting of HU, IKT, egg yolk weight, egg white weight, egg weight egg, shell thickness, and egg shape index. The study concluded that nanochitosan can be used as a feed additive to improve the physical quality of eggs in pengging ducks. The use of nanochitosan with different levels as a feed additive can be useful for others by providing a reference about the levels of nanochitosan used as a feed additive which can improve the physical quality of duck eggs and become important information in increasing exploration in the use of nanochitosan products. This study is expected to open opportunities for further research in the future about the mechanistic effects of nanochitosan in improving egg quality and productivity of laying ducks.